COMPARISON OF PEDAGOGICAL QUALIMETRY WITH TRADITIONAL METHODS OF ASSESSING THE KNOWLEDGE OF HIGH SCHOOL STUDENTS - Abdulkhafizov Bunyod Khakimjonovich (International Scientific and Current Research Conferences, 2023)
This article is a study aimed at a comparative analysis of the effectiveness of pedagogical qualimetry and traditional methods of assessing the knowledge of high school students. Pedagogical qualimetry is a modern approach to the assessment of educational achievements based on the use of computer technologies, analytical methods and data. The article discusses the basic principles and methods of pedagogical qualimetry, as well as its potential for improving the educational process. The authors conduct a comparative study of the results of the use of pedagogical qualimetry and traditional methods of assessing the knowledge of high school students based on data collected in a real educational environment. Parameters such as the accuracy of assessments, objectivity, time spent on assessment, and the degree of motivation of students are analyzed.